A dance like starlight : one ballerina's dream - Dempsey, Kristy (Philomel Books, an imprint of Penguin Group (USA), 2014)
A young girl growing up in Harlem in the 1950s, whose mother cleans and stitches costumes for a ballet company, dreams of becoming a prima ballerina one day, and is thrilled to see a performance of Janet Collins, the first "colored" prima ballerina.